Impact of Therapeutic Community Training on Knowledge and Attitudes of Correctional Officers - Dr., Medha Talpade (International Journal of Psychosocial Rehabilitation, 2013)
Therapeutic Communities (TCs) have demonstrated success in providing inmates with a second chance in life. This study is an evaluation of TC training of correctional officers. A mixed methods strategy was employed, informed by the attribution theory and the self-determination theory, whereby it is assumed that changing the knowledge and attitudes of the officers would have a positive effect on the motivation of the inmates. In this study, the impact of the training on the knowledge gained and at-titudes changed were gauged. A total of 63 officers received TC training. Results of an open ended survey were coded into themes. Additionally, self efficacy of the officers was assessed quantitatively, regarding their use of TC concepts. Validation strategies included inmate responses about treatment by the officers. Results indicated that officers recognized the need for a cognitive shift about authority in the jail and in the attitudes toward the inmates. Validation by the inmates as documented by their pos- itive beliefs about the officers, further confirmed this shift in knowledge and attitudes. Implications for positive social change, by reducing recidivism, rehabilitating inmates into becoming productive members of the community and fostering the growth of safer communities are imminent